The chemical conditions of the late Archean Hamersley basin inferred from whole rock and pyrite geochemistry with Δ33S and δ34S isotope analyses. (15th January 2015) - Gregory, Daniel D.; Large, Ross R.; Halpin, Jacqueline A.; Steadman, Jeffery A.; Hickman, Arthur H.; Ireland, Trevor R.; Holden, Peter
Abstract: The well-preserved late Archean sedimentary rocks of the Fortescue and Hamersley Basins in Western Australia offer fascinating insights into early earth ocean chemistry prior to the Great Oxidation Event (GOE). In this study, we use a combination of whole rock geochemistry, LA-ICPMS trace element analysis of sedimentary pyrite and pyrrhotite and SHRIMP-SI sulfur isotope analyses to elucidate the chemical changes in these sedimentary rocks. These proxies are used to examine chemical conditions of the ocean during the late Archean. Two to three periods of oxygen enrichment prior to the deposition of banded iron formations (BIF) can be identified. One minor stage of general increase in whole rock enrichment factors and trace element content of pyrite is observed up stratigraphy in the Jeerinah Formation, Fortescue Basin and a more substantial stage is present in the Paraburdoo and Bee Gorge Members of the Wittenoom Formation, Hamersley Basin. Some of the trace element enrichments indicate organic matter burial flux (Ni, Cr, Zn, Co and Cu) which suggests an increase in biological productivity. If the increased biological activity reflects an increase in cyanobacteria activity then an associated increase in oxygen is likely to have occurred during the deposition of the Bee Gorge Member. An increase in atmospheric oxygen would result in continental weathering of sulfide and other minerals, increasing the trace element content of the water column via erosion and avoiding excessive depletion of trace elements due to drawdown in seawater. Since some of these trace elements may also be limiting nutrients (such as Mo and Se) for the cyanobacteria, the degree of biological productivity may have further increased due to the increasing amount of trace elements introduced by oxygenation in a positive feedback loop. These periods of increased productivity and oxygen rise stopped prior to the onset of BIF deposition in the Hamersley Basin. This may be due to the ocean reaching an oxidation threshold, enabling the precipitation of hematite and magnetite BIF. The BIF deposition caused depletion of ocean nutrients such as phosphate, severely limiting the growth of cyanobacteria, and thus limiting further oxygen production.